Fennoscandia before Nuna/Columbia: Paleomagnetism of 1.98–1.96 Ga mafic rocks of the Karelian craton and paleogeographic implications - Lubnina N.; Pisarevsky S.; Stepanova A.; Bogdanova S.; Sokolov S. (2017)
© 2017 Elsevier B.V.Numerous mafic dykes, sills and intrusions with ages between 1985 Ma and 1960 Ma are exposed near the Onega Lake in southern Karelia, Russia. The paleomagnetic analysis of these rocks has revealed a stable remanence with directions belonging to two groups. The directions of the first group characterize ten intrusions including the dated 1970 ± 3 Ma Unoi sill and 1976 ± 9 Ma Suna River Canyon dolerite, the corresponding paleomagnetic pole is 44.4°N, 101.5°E, A95 = 6.3°. The second group comprises two intrusions including the 1984 ± 8 Ma Pudozhgora intrusion and Krestoviy Navolok dyke with the corresponding paleopole calculated from 5 site mean poles is 60.9°N, 144.8°E, A95 = 6.8°. Both remanence directions are supported by robust baked contact tests. We propose the first group's pole as the key 1975 Ma Fennoscandian pole. The second one is well dated, but based only on two intrusions without proper averaging of the paleosecular variations. We have also carried out a complimentary paleomagnetic study of the previously investigated 2504 Ma Shalskiy gabbronorite dyke. The remanence of this dyke is now supported by the inverse contact test and statistics can be improved. Using our 1975 Ma pole together with coeval poles from Superior, Slave and Amazonia cratons we propose a provisional 1975 Ma paleogeographic reconstruction.